Adaptive controlled superconducting magnetic energy storage devices for performance enhancement of wind energy systems - Rania A. Turky; Tarek S. Abdelsalam; Hany M. Hasanien; Mohammed Alharbi; Zia Ullah; S.M. Muyeen; Amr M. Abdeen (Ain Shams Engineering Journal, 2023)
This research paper introduces the Generalized Continuous Mixed P-Norm Sub-Band Adaptive Filtering (GCMPNSAF) algorithm, designed for efficient online control of Superconducting Magnetic Energy Storage Devices (SMESDs) in Wind Energy Systems (WESs). The primary objective of this algorithm is for minimizing power ripples in WESs. The Wind Energy System (WES) under consideration is tied to the IEEE 39 bus system, with the Superconducting Magnetic Energy Storage Device (SMESD) integrated at the point of common coupling. The GCMPNSAF algorithm is applied to update or adapt proportional-integral (PI) controller gains of SMESD interface circuits. The proposed algorithm is an enhanced version of the CMPN by adding the sub-band filtering algorithm effect. It depends mainly on the actuating error signal, and it has a variable step size of the CMPN. The detailed modeling of the whole system is presented, including measured wind speed data, detailed switching techniques, a drive train model of the turbine, and real SMESD. The efficacy of the proposed SMESD has been validated through a comparative analysis with the Least Mean Square-SMESD approach, under conditions of varying and unpredictable wind speeds. The simulation results produced by the PSCAD software are used to evaluate the study's validity. The utilization of controlled SMESDs has the potential to significantly enhance the power quality of WESs.